Can the Calculator Clinic Deter Hypoglycemia, Prevent Hypoglycemia in Hemodialysis Patients, and Reduce D40% Use? - Anindhita, Rakhma; Kiswanto, Agus; Noviana, Siska Andika; Juwandi, Juwandi; Darmawan, Rendi Editya (Indonesian Basic and Experimental Health Sciences, 2025)
IntroductionHypoglycemia is a common complication in diabetic nephropathy (DN) patients undergoing hemodialysis. Early detection is essential to prevent adverse outcomes. A calculator-based clinical tool (cyclic hypoglycemia calculator) was developed to estimate hypoglycemia risk and guide additional glucose needs. This study aimed to analyze the effect of using the calculator on preventing hypoglycemia during hemodialysis. MethodsA quasi-experimental pre–post test control group design was conducted among hemodialysis patients at Dr. Moewardi Hospital (March–July 2024). Samples were selected via simple random sampling: odd medical record numbers for the control group and even numbers for the intervention group. The intervention group received hypoglycemia-risk calculation and glucose adjustment recommendations, while the control group followed standard procedures. Blood glucose levels were measured before and after 4-hour hemodialysis using a standardized glucometer. Data were homogeneous (P=0.903) and non-normally distributed (P=0.00), so the Mann–Whitney test was applied. ResultsThere was no significant difference in blood glucose levels between groups (P=0.811). Pre-dialysis glucose levels were similar (115.45 vs. 114.71 mg/dL), and post-dialysis levels remained comparable (99.39 vs. 98.21 mg/dL). In the control group, 33% experienced increased glucose, 3% remained unchanged, and 64% decreased, with an average reduction of 33.67 mg/dL. In the intervention group, 36% increased and 64% decreased, with an average reduction of 24.5 mg/dL. ConclusionsThe hypoglycemia-deterrent calculator did not produce significant differences in glucose levels compared with standard care. However, its use showed 75% efficiency in reducing unnecessary D40% administration. Further studies are recommended to refine D40% dosing strategies during hemodialysis based on individualized risk scoring.